PRODUK KERAMIK STONEWARE DENGAN KONSEP FRONTO DI THE FRONTIER HOUSE - Satrio Hutomo, Adam; Mudra, I Wayan; Muka, Muka (Pusat Penerbitan LPPM ISI Bali, 2024)
Fronto is a concept to create a functional ceramic work for the needs of the coffee shop at The Frontier House which is a partner in completing an independent project in the Merdeka Learning Independent Campus (MBKM) program. Fronto is a mascot from The Frontier House in which Fronto is a dinosaur (T-Rex). Fronto is embodied by an upright posture and holding a cup in his right hand, has a simplified shape, wears a raglan shirt with the F logo on his chest and complete with his pants and shoes. The costume from Fronto is inspired by the costume of American students in the 70s, with the hope that The Frontier House's coffee shop business can remain standing, become big, and everlasting. Based on this, the author got the idea to create a functional ceramic product that can be directly applied to The Frontier House coffee shop business, as a realization of an agreement with MBKM partners. Using creation methods such as observation methods for introduction, exploration methods for exploring ideas, design design methods to illustrate clearly, and work creation methods for the execution stage, with embodiment techniques applying rotation techniques, pinching techniques, and cast printing techniques. The result is the creation of two types of incense holders, glasses, ashtrays, and succulent pots by applying the elements contained in Fronto into the form of ceramic works, by applying vintage colors, namely olive green and orange in accordance with the color concept applied by The Frontier House, thus producing harmony between ceramic products made with The Frontier House concept which can provide comfort and interest for visitors.